Colonoscopy is safe and not associated with higher pain scores in patients with hypermobility spectrum disorder: results from an exploratory prospective study. (July 2020) - Beckers, Abraham B.; Vork, Lisa; Fikree, Asma; de Ridder, Rogier; Aziz, Qasim; Masclee, Ad; Keszthelyi, Daniel
Background: Patient perception of colonoscopy varies greatly. Young slender women and patients with irritable bowel syndrome (IBS) appear to be at risk for periprocedural pain. Recent evidence suggests a high prevalence of joint hypermobility related connective tissue disorders in this population. Therefore, we aimed to investigate whether hypermobility spectrum disorder (HSD) is associated with increased pain during colonoscopy. Methods: We prospectively included patients undergoing routine colonoscopy. Subjects were assessed for HSD using the 2017 criteria, and IBS and functional dyspepsia using the Rome III criteria. After colonoscopy and recovery from sedation, patients were asked to report pain scores on a 100-mm visual analogue scale (VAS). In addition, caecal intubation time was measured, endoscopists scored the difficulty of the procedure (100-mm VAS) and procedure-related adverse events were registered. Results: Of 200 included patients, 22 (11%) met criteria for HSD. A female predominance was observed in patients with HSD (86.4% versus 49.4%, p < 0.001). A crude linear regression model demonstrated that pain scores were 13.30 mm higher in patients with HSD versus non-HSD patients (95% CI 0.07 – 26.53, p = 0.049). When subsequently correcting for possible confounding factors, however, this difference in pain scores could be explained by a confounding effect of female gender. Caecal intubation time, perceived procedural difficulty and complication rate did not differ significantly between groups. Conclusion: HSD does not seem to be a predictor of painful colonoscopy, probably due to female gender as a confounding factor. In addition, performing colonoscopy is not more complicated in patients with HSD versus non-HSD patients, nor is it associated with more adverse events.